Giant Tuberculosis Verrucosa Cutis - Abu Baker; Farzana Akhter; Rokon Uddin (Our Dermatology Online, 2012)
A 38year old man had asymptomatic slowly progressive warty lesion on extensor surface of left elbow and arm for about 20 years. Examination revealed larger one sized of 16cm×15cm and smaller one about 8cm×5cm. Lesions were Keratotic, verrucous, nontender, cauliflower-like indurated plaque. Mantoux test resulted 20mm×18mm on 48 hours observation. Histopathological examination of the lesion showed epitheloid cell granuloma with giant cells and lymphocytes in the mid dermis. The conclusive diagnosis was tuberculosis verrucosa cutis based on above findings. Six month therapy with INH 300mg plus Rifampicin 600mg supplemented initial 2 months ethambulol 1000mg plus pyrazinamide 1500mg daily resulted complete clearance of the lesions.